The necessity of bilateral staging bone marrow examinations for paediatric solid tumours - Anne-Cecilia van Marle; Ilse Coetzee; Wynand Britz; Jade Eichbauer; Marguerité Smith; Marli van Gend; Helen van der Westhuizen; Rièlle Vorster; Leriska Haupt (South African Journal of Oncology, 2022)
Background: Bone marrow aspirates and trephine biopsies (BMATs) form an important part of staging to detect bone marrow metastases of both haematological and nonhaematological neoplasms.